What it is like to go to war - Marlantes, Karl (Atlantic Monthly Press, 2011)
War is as old as humankind, but in the past, warriors were prepared for battle by ritual, religion and literature, which also helped bring them home. In this narrative, the author weaves accounts of his combat experiences with thoughtful analysis, self-examination, and his readings from Homer to the Mahabharata to Jung. He talks frankly about how he is haunted by the face of the young North Vietnamese soldier he killed at close quarters and how he finally finds a way to make peace with his past. He discusses the daily contradictions that warriors face in the grind of war, where each battle requires them to take life or spare life, and where they enter a state he likens to the fervor of religious ecstasy. He also underscores the need for returning veterans to be counseled properly.